Les seigneuresses de l'île - Barthe, Marcel (Les Argoulets, 2024)
Keywords: Congrégation de Notre-Dame; Femmes; Île-des-Soeurs

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Quand l'art prend la rue - Bilodeau, Maxime (Continuité, 2024)
issued: 2024-23-00
Keywords: Monuments; Places publiques

Le fort de Verdun localisé - Dubeau, Pierre (Les Argoulets, 2024)
Keywords: Forts; Verdun

L'émergence et la transformation des interfaces ville-industrie: Le cas de la planification urbaine d'Assomption Sud-Longue-Pointe à Montréal - Lambert, Olivier (Université du Québec à Montréal, 2024)
Keywords: Longue-Pointe

Passé et avenir d'une rivière montréalaise - Legault, Louise (Histoire Québec, 2024)
Keywords: Lachine; Lachine (canal); Pollution; Égouts

The High Ground: Mansions, Mythology, and the Mountain - Macleod, Roderick (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Paysages; Quartiers

La vie de John Elsdale Molson - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont

La rue Saint-Denis (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-21-00
Keywords: Cherrier; Côme-Séraphin; Hôpital Sainte-Justine; Levasseur; Irma; Massicotte; Édouard-Zotique; Patrimoine; Plateau Mont-Royal (arrondissement); Saint-Denis (rue)

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

L’ancien cimetière Saint-Antoine (1799-1854) et son voisin rural à Pointe-aux-Trembles (1709-1843) : analyse comparative de la mortalité des enfants de deux populations du XIXe siècle sur l’île de Montréal - Duchemin, Emmanuelle (Université de Montréal, 2023)
Keywords: Enfants; Mortalité; Pointe-aux-Trembles; Saint-Antoine

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Le mystère urbain de Crawford Park. Des origines à la Dépression- (Partie 1) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

L'Hôtel de ville a 130 ans. La fabuleuse histoire de la mairie d'Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
issued: 2023-21-00
Keywords: Hôtel de ville; Outremont; Patrimoine

Une mesure d'origine britannique. Les barrières à péage à Outremont - Waché, Gabriel; Bizier, Hélène-Andrée (Mémoire vivante, 2023)
issued: 2023-21-00
Keywords: Outremont; Routes

Les débuts de la poste à Ahunstic-Cartierville - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Bordeaux; Cartierville; Poste; Sault-au-Récollet

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n84 Translators: _:n62458
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

St Anne's Market. A Long-Awaited Project - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n73 Translators: _:n62480
Keywords: Marchés; Sainte-Anne (marché)

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Translators: _:n461 Translators: _:n62043
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

For Our Collective Heritage. Nothing Is Loss Forever - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n199 Translators: _:n62269
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

A Building Transformed. From Market to Parliament - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n106 Translators: _:n62380
Keywords: Marchés; Parlement; Sainte-Anne (marché)

Discovering Parliament in Montréal - Gignac, François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n230 Translators: _:n62369
Keywords: Parlement

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Choléra; Épidémies

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n62 Translators: _:n62435
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Aux origines du village de Saint-Jean-Baptiste, 1850-1861 - Robert, Jean-Claude (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n95 Translators: _:n62402
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n38 Translators: _:n62447
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-23-00
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

The Goode House (The Westmount Historian, 2021)
Number: 2
Keywords: Conservation; Famille; Jardins; Patrimoine

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Number: 2
Keywords: Jardins

L'homme aux 300 clochers - Anctil, Gabrielle (Continuité, 2021)
issued: 2021-23-00
Keywords: Bourgeau; Victor; Églises

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Au marché Sainte-Anne (1834-1844). Produits... et réunions de toutes sortes - Burgess, Joanne (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

Le marché Sainte-Anne. Un projet depuis longtemps souhaité - Burgess, Joanne (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

The Goode House: A Special Place - Cameron, Christina (The Westmount Historian, 2021)
Number: 2
Keywords: Conservation; Patrimoine

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Pour la mémoire collective. Rien n'est jamais perdu - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché)

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

Les paysages urbains historiques des canaux de Lachine et de Chambly: une démarche exploratoire. - Gelly, Alain; Paradis, Mathieu (Paysages du mouvement/paysages en mouvements: Trajectoires, perspectives et panoramas, 2021)
Keywords: Lachine (canal)

À la découverte du parlement de Montréal - Gignac, François (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Parlement

La transformation d'un bâtiment. De marché à parlement - Gignac, François (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Parlement; Sainte-Anne (marché)

À l'ombre de la montagne : le paysage archéologique du versant nord du mont Royal, Montréal, 1698-1900 - Janssen, Valérie (Université de Montréal, 2021)
Keywords: Cimetières; Mont-Royal (parc)

Un monument précurseur dans la définition d’une nouvelle identité architecturale dans le diocèse catholique romain de Montréal - Noppen, Luc (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Number: 1
Keywords: Bourgeau; Victor; Sainte-Brigide (paroisse); Églises

Urban Picturesque. John James Browne and the Fire Stations of Montréal - Osborne, John (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Number: 1
Keywords: Casernes; Pompiers

Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Translators: _:n117 Translators: _:n62493
Keywords: Métropole; Port

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

1844-1849. Montréal, nouveau siège du gouvernement - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

De part et d'autre de la Petite rivière. Montréal naît et grandit - Stewart, Alan (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Faubourgs; Fortifications; Forts

On Both Shores of the Little River. Montréal Emerges and Evolves - Stewart, Alan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Translators: _:n241 Translators: _:n62316
Keywords: Faubourgs; Fortifications; Forts

Synagogue Architecture in Canada: A Summary History - Stiefel, Barry L. (Journal of the Society for the Study of Architecture in Canada, 2021)
Keywords: Juifs

Square Saint-Louis: Lieu mythique (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
issued: 2020-21-00/2020-22-00
Keywords: Librairie; Miron; Gaston; Monuments; Nelligan; Émile; Places publiques; Poésie; Squares; École littéraire de Montréal; Écrivains

La mutation vers un espace urbain moderne. Le projet de démantèlement des fortifications de Montréal - Beauchamp-Monfette, Joel (Cap-aux-Diamants, 2020)
issued: 2020-24-00
Keywords: Fortifications

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (McGill-Queen's University Press, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Du couvent des Dames du Sacré-Cœur à l’école secondaire Sophie-Barat. État des lieux d’une institution pionnière - M. Sénécal, Geneviève (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 7
Keywords: Communautés religieuses

Le canal de Lachine: un paysage en constant mouvement - Paradis, Matthieu; Gelly, Alain (Histoire Québec, 2020)
Number: 4
Keywords: Lachine (canal); Paysages

La maison Nivard-De-Saint-Dizier au temps de John Crawford, haut lieu de chasse à courre - Tremblay Lamarche, Alex (Cap-aux-Diamants, 2020)
issued: 2020-22-00
Keywords: Chasse à courre; Clubs; Crawford; John; Montreal Hunt Club; Nivard-De-Saint-Dizier (maison); Verdun

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 6
Keywords: Incendies; Routes; Rues

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

Le recours aux technologies numériques pour l'étude de contenus à caractère historique et archéologique: l'exemple du site de l'ancien marché Sainte-Anne et du Parlement de la province du Canada - Charbonneau, Nathalie; Thirion, Anna (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Archéologie; Histoire; Marchés; Parlement; Patrimoine; Sainte-Anne (marché)

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; Parcs; Travail

Le patrimoine architectural résidentiel de la Pointe-aux-Trembles ou Les belles Pointelières - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2019)
Keywords: Patrimoine; Pointe-aux-Trembles; Quartiers

Les jardiniers professionnels de Montréal au XVIIIe siècle - Fortin, Guillaume (Université du Québec à Montréal, 2019)
Keywords: Jardins; Travail

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

"To muse within these peaceful portals": Urban Space, Public Order, and the Makings of Montreal’s Viger Square, 1818-1870 - Horner, Dan (Violence, Order, and Unrest: A History of British North America, 1749-1876, 2019)
Reporter: Violence, Order, and Unrest: A History of British North America, 1749-1876
Keywords: Carré Viger; Marchés; Places publiques; Squares

Le pollen, de la protohistoire à l'ère industrielle. Paysage végétal et société à la pointe à Callière, Montréal, vers 1590 à 1879 - Juteau, Audrée (Université de Montréal, 2019)
Keywords: Flore; Jardins; Paysages; Pointe-à-Callière

Témoins discrets - Leclerc, Jean-François (Continuité, 2019)
issued: 2019-24-00
Keywords: Chinois; Grecs; Irlandais; Italiens; Juifs; Noirs; Patrimoine; Syriens

L'art de la gravure entre 1850 et 1885 et l'architecture commerciale de Montréal : le cas de John Henry Walker - Sirois, Hélène (Université du Québec à Montréal, 2019)
Keywords: Gravure; Publicité; Walker; John Henry

" Je me souviens " d’un domaine seigneurial à Ahuntsic - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Communautés religieuses; Domaine Saint-Sulpice; Logement; Seigneurie; Sulpiciens

Commerces du Plateau: d'hier à aujourd'hui (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-24-00/2019-24-00
Keywords: Alimentation; Artisans; Bijouterie; Chaussure; Commerce de détail; Magasins; Mont-Royal (rue); Plateau Mont-Royal; Quartiers; Quincaillerie; Rues; Saint-Denis (rue); Saint-Laurent (rue); Épicerie

La résidence des Jésuites: lieu de justice à Montréal de 1765 à 1800 - Barbe, Raoul P. (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Communautés religieuses; Jésuites; Palais de justice

Le premier vrai palais de justice au Canada - Barbe, Raoul P. (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Incendies; Palais de justice; Patrimoine; Prisons

Le vieux palais de justice de Montréal - Caron, Denise (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Avocats; Juges; Palais de justice; Parlement; Patrimoine

Peopling and Organizing the Island of Montreal: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Villages

The Modern City: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

L'histoire des palais de justice montréalais - Landry, Johanne (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Conservation; Palais de justice; Patrimoine

Vieux palais de justice et protection du patrimoine culturel - Lizotte, Sylvain (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Conservation; Palais de justice; Patrimoine; Vieux-Montréal

Montreal Old Cemeteries - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Cimetières

Mount Royal: The Top of the Island - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

Montreal and Its Natural Environment - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Climat; Géographie physique; Voie maritime

Managing and Analyzing Archaeological Data with GIS: the Case of Place D’Youville, Montréal - Robichaud, Léon; Van Gijseghem, Hendrik; Petit, Kim; Burgess, Joanne (Proceedings of the 3rd Digital Heritage International Congress and 2018 24th International Conference on Virtual System & Multimedia, 2018)
Reporter: Proceedings of the 3rd Digital Heritage International Congress and 2018 24th International Conference on Virtual System & Multimedia
Keywords: Archéologie; Histoire; Places publiques; Youville (place d')

De siège du gouvernement à capitale éphémère: Kingston, Montréal et le passage à l’État libéral moderne (1838–1849) - Roy, Alain (Urban History Review / Revue d'histoire urbaine, 2018)
issued: 2018-21-00
Keywords: Gouverneurs; Parlement

Le " vieux " palais de justice de Montréal, témoin d'un projet de capitale, 1838-1850 - Roy, Alain (Le patrimoine bâti judiciaire de Montréal, 2018)
Keywords: Palais de justice; Parlement; Patrimoine

L'architecture du Plateau Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
issued: 2017-23-00
Keywords: Carmélites; Communautés religieuses; Logement; Plateau Mont-Royal; Quartiers; Églises

Montréal, par rues et par ruelles - Archambault-Malouin, Diane (Histoire Québec, 2017)
Number: 1
Keywords: Rues; Toponymie

The LaFontaine House, a presentation about a thirty year campaign (to date) to acquire the LaFontaine House in Montreal so that could become a National Monument in Canada (Abstract - Résumé) - Fish, Michael (Histoire Québec, 2017)
Number: 1
Keywords: Conservation; La Fontaine; Louis-Hippolyte; Patrimoine

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Number: 1
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

L’ancien square Dominion à Montréal: un parcours d’art et d’histoire - Joly, Diane (Histoire Québec, 2017)
Number: 4
Keywords: Dominion (square); Idéologies; Monuments; Places publiques; Squares

Sound, Deindustrialization, and Gentrification: The Changing Aural Landscape of Pointe-Saint-Charles - Luderowski, Muriel (Université Concordia, 2017)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

The Urban Horse and the Shaping of Montreal, 1840–1914 - Olson, Sherry (Animal Metropolis: Histories of Human-Animal Relations in Urban Canada, 2017)

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Le Parlement du Canada-Uni à Montréal, 1843-1849: Un site archéologique exceptionnel - Pothier, Louise; Van Gijseghem, Hendrik (Revue parlementaire canadienne, 2017)
issued: 2017-24-00
Keywords: Archéologie; Marchés; Parlement; Sainte-Anne (marché)

Beautiful Cities - Weinberg, Paul (Canada's History, 2017)
Number: 6
Keywords: Mont-Royal (parc)

Alimentation, commerce et patrimoine: documenter les acteurs du Vieux-Montréal victorien 1850-1880 - Burgess, Joanne (Laboratoire d'histoire et de patrimoine de Montréal, 2016)
Keywords: Alimentation; Commerce de détail; Magasins; Patrimoine; Quartiers; Vieux-Montréal

Une ville fortifiée - Bélanger, Christian (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts

150 ans d’histoire militaire au centre-ville de Montréal - Joly, Diane (Revue militaire canadienne, 2016)
issued: 2016-24-00
Keywords: Dominion (square); Guerre; Monuments; Places publiques; Squares

Les 150 ans du Gesù (1865-2015) - Lapierre, Michel (Montréal en tête, 2016)
issued: 2016-23-00
Keywords: Communautés religieuses; Gesù; Jésuites; Saint-Joseph (maison); Églises

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

From desintegration to reinterpretation: urban design in Montreal, 1950-2014 - Racine, François (City as organism: new visions for urban life, 2016)
Keywords: Cartes et plans

Belles demeures historiques de l'île de Montréal - Rémillard, François; Merrett, Brian (Les Éditions de l'Homme, 2016)
Keywords: Patrimoine

Au temps où l'île Sainte-Hélène était militaire - Royer, Martin (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Fortifications; Forts; Île Sainte-Hélène

" Il y a déjà assez et trop de gothique à Montréal " Patrick C. Keely et la construction de l’église du Gesù de Montréal - Sauvé, Jean-Sébastien (Journal of the Society for the Study of Architecture in Canada / Journal de la société pour l'étude de l'architecture au Canada, 2016)
Number: 2
Keywords: Communautés religieuses; Gesù; Jésuites; Églises

L’église du Gesù de Montréal. Histoire d’un bâtiment singulier - Sauvé, Jean-Sébastien (Le Gesù, 150 ans d’histoire, 2016)
Keywords: Communautés religieuses; Gesù; Jésuites; Patrimoine; Églises

Dans le jardin des sulpiciens, seigneurs de l'île - Vaillancourt, Pascale (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Communautés religieuses; Jardins; Sulpiciens

Urban Environments and the Animal Nuisance: Domestic Livestock Regulation in Nineteenth-Century Canadian Cities - Kheraj, Sean (Urban History Review / Revue d'histoire urbaine, 2015)
issued: 2015-23-00/2016-21-00

100 tonnes d'explosifs stockés sur l'avenue Dunlop! Intolérable! - Lester, Normand (Mémoire vivante, 2015)
issued: 2015-24-00/2016-24-00
Keywords: Armes; Forts; Rébellions

Les spectacles sur scène à Montréal, avant la Place des Arts - Montpetit, Raymond (50 ans de la Place des Arts, 2015)

Beyond Brutal Passions. Prostitution in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (McGill-Queen's University Press, 2015)
Keywords: Femmes; Prostitution

Montreal's Golden Square Mile: a historical perspective - Smith, Mackay L. (InfiniteBooks, 2015)
Keywords: Golden Square Mile; Quartiers

Au temps des chevaux et des rails (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2014)
issued: 2014-22-00
Keywords: Automobile; Chemins de fer; Chevaux; Cyclisme; Funiculaire; Gares; Groupes populaires; Mont Royal; Plateau Mont-Royal; Quartiers; Tramways; Transport en commun

Heritage Sites (The Westmount Historian, 2014)
Number: 2
Keywords: Cimetières; Patrimoine; Rues; Saint-Antoine; Westmount

Une banque dans Hochelaga - l'immeuble de la Fondation Guido Molinari (Fondation Guido Molinari, 2014)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques; Hochelaga (quartier); Quartiers

Les écrits urbains sous contrôle. L'exemple de Montréal - Artières, Philippe (Presses Universitaires de Rennes, 2014)
Keywords: Enseignes; Français; Publicité

Maison-des-Marins: de la mer au musée - Dagenais, Dominic (Continuité, 2014)
issued: 2014-24-00
Keywords: Musée Pointe-à-Callière

Historique architectural et social du bâtiment - Déom, Claudine (Une banque dans Hochelaga - l'immeuble de la Fondation Guido Molinari, 2014)
Keywords: Banque d'épargne de la cité et du district de Montréal; Banques; Hochelaga (quartier); Quartiers

Entre champ d'intérêt et objet de pression, le patrimoine. Les luttes pour la conservation du Château Ramezay, 1893-1932 - Hébert, Karine (De la représentation à la manifestation. Groupes de pression et enjeux politiques au Québec, XIXe et XXe siècles, 2014)
Keywords: Conservation; Patrimoine; Ramezay (château de)

Des milieux de vie animés dans une ville en transformation rapide - Linteau, Paul-André (Quartiers disparus: Red Light, Faubourg à M'lasse, Goose Village, 2014)
Keywords: Quartiers

Quartiers disparus: Red Light, Faubourg à M'lasse, Goose Village - Linteau, Paul-André; Charlebois, Catherine (Les Éditions Cardinal, 2014)
Keywords: Drapeau; Jean; Faubourgs; Logement; Maires; Quartiers

A Community of Believers and Healers: Learning from the functional characteristics of Hôtel Dieu - McDonald, Marie-Pierre (Université McGill, 2014)
Keywords: Communautés religieuses; Hôpitaux; Hôtel-Dieu

La chapelle historique du Bon-Pasteur: la maison de la musique - Nicholson, Georges (Druide, 2014)
Keywords: Communautés religieuses; Musique

TAYLOR, sir ANDREW THOMAS - Wagg, Susan (Dictionnaire biographique du Canada, 2014)

Sur les traces de Joseph Venne, architecte, 1858-1925 - Bassil, Soraya; Allard, Michel; Binette, René (Septentrion, 2013)

Forme et sens des squares victoriens montréalais dans le contexte de développement de la métropole (1801-1914). 2 tomes - Cha, Jonathan (Université du Québec à Montréal, Institut national de la recherche scientifique et Institut d'urbanisme de Paris - Université Paris-Est, 2013)
Keywords: Squares

Forme et sens des squares victoriens montréalais dans le contexte de développement de la métropole (1801-1914). Volume II - Cha, Jonathan (Université du Québec à Montréal, Institut national de la recherche scientifique et Institut d'urbanisme de Paris - Université Paris-Est, 2013)
Keywords: Squares

Wildlife, Conservation, and Conflict in Quebec, 1840-1914 - Ingram, Darcy (University of British Columbia Press, 2013)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Sulpician Cultural Strategies: Architecture - Lachapelle, Jacques (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46524
Keywords: Communautés religieuses; Sulpiciens

The Sulpicians and the Montreal Space - Robert, Jean-Claude (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46434
Keywords: Communautés religieuses; Sulpiciens

Marché Sainte-Anne. Bilan des connaissances - Trépanier, Mathieu (Laboratoire d'histoire et de patrimoine de Montréal, 2013)
Keywords: Marchés; Sainte-Anne (marché)

Évolution du patrimoine architectural religieux du territoire historique de la Pointe-aux-Trembles - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2012)
Keywords: Patrimoine; Pointe-aux-Trembles; Quartiers; Églises

Montreal, City of Spires: Church Architecture during the British Colonial Period, 1760-1830 - Epstein, Clarence (Presses de l'Université du Québec, 2012)
Keywords: Églises

Les jardins d'agrément en Nouvelle-France. Étude historique et cartographique - Fortier, Marie-Josée (Les Éditions GID, 2012)
Keywords: Jardins

La ville moderne, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Organisation et peuplement de l'île à l'extérieur de Montréal, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Villages

Montréal et son environnement naturel - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Climat; Géographie physique; Voie maritime

The Political Ecology of Floods in the Late Nineteenth Century - Boone, Christopher G. (Metropolitan Natures: Environmental Histories of Montreal, 2011)

Metropolitan Natures: Environmental Histories of Montreal - Castonguay, Stéphane; Dagenais, Michèle (University of Pittsburgh Press, 2011)

The Colonial Landscapes of the Early Town - Coates, Colin M. (Metropolitan Natures: Environmental Histories of Montreal, 2011)

At the Source of a New Urbanity: Water Networks and Power Relations in the Second Half of the Nineteenth Century - Dagenais, Michèle (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc

Une ville et son fleuve. Montréal vue/s de l'eau - Dagenais, Michèle (La ville: phénomène de représentation, 2011)

The Herons Are Still Here: History and Place - Dickenson, Victoria (Metropolitan Natures: Environmental Histories of Montreal, 2011)

Surface Water in the Early Nineteenth Century - Fougères, Dany (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc; Égouts

La première église Notre-Dame de Montréal: l'architecture d'un monument disparu - Lachapelle, Jacques (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2011)
Keywords: Notre-Dame (église); Églises

Querelle "monumentale" à propos de l'héritage patriote - Laporte, Gilles (Montréal en tête, 2011)
issued: 2011-22-00
Keywords: Cimetières; Duvernay; Ludger; Institut canadien; Monuments; Notre-Dame-des-Neiges (cimeitère); Rébellions; Société Saint-Jean-Baptiste; Églises

City Streets as Environmental Grid: The Challenge of Private Uses and Municipal Stewardship - Olson, Sherry (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Rues

Hidden Water in the Landscape: The Covered Reservoirs of Mount-Royal - Ross, Susan M. (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc; Mont Royal

Montreal Up in Smoke: A Spatial Analysis of Mid-Nineteenth Century Urban Fires - Spencer, Pheobe (Université McGill, 2011)
Keywords: Incendies

Le moulin de Pointe-Claire, 1710-2010 / 1710-2010, The Pointe-Claire Mill - Arsenault, Claude (Société pour la sauvegarde du patrimoine de Pointe-Claire, 2010)
Keywords: Meunerie; Pointe-Claire

Le moulin à vent de Pointe-aux-Trembles - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles avec le concours de l'arrondissement Rivière-des-Prairies - Pointe-aux-Trembles de la ville de Montréal, 2010)
Keywords: Conservation; Meunerie; Patrimoine; Pointe-aux-Trembles

La rue Sainte-Catherine: au cœur de la vie montréalaise - Linteau, Paul-André (Éditions de l'Homme et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2010)
Keywords: Rues; Sainte-Catherine (rue)

Sainte-Catherine Street: at the Heart of Montréal Life - Linteau, Paul-André (Éditions de l'Homme et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2010)
Translators: _:n42654
Keywords: Rues; Sainte-Catherine (rue)

À la recherche des premiers Montréalais. Le cimetière de la première église Notre-Dame de Montréal - Balac, Anne-Marie (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2009)
Keywords: Cimetières; Notre-Dame (paroisse); Notre-Dame (église); Églises

Une présence symbolique. Le « monument aux Patriotes » du cimetière Notre-Dame-des-Neiges - Brodeur, Mario (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2009)
Keywords: Cimetières; Conservation; Monuments; Notre-Dame-des-Neiges (cimetière); Rébellions

The Urbanization of Nature: Water Networks and Green Spaces in Montreal - Dagenais, Michèle (Method and Meaning in Canadian Environmental History, 2009)
Keywords: Aqueduc; Parcs; Égouts

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

La reconstruction d’un monument historique. La maison Simon-Lacombe au cimetière Notre-Dame-des-Neiges - Gallant, Conrad (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2009)
Keywords: Cimetières; Conservation; Monuments; Notre-Dame-des-Neiges (cimetière)

Montréal, une île des villes - Paquette, Marcel (Les Éditions GID, 2009)
Keywords: Villages

Le fort et les poudrières du complexe militaire de l'île Sainte-Hélène - Royer, Martin (Université Laval, 2009)
Keywords: Armes; Fortifications; Forts; Île Sainte-Hélène

Preservation of Westmount Homes built in the 1800s (The Westmount Historian, 2008)
Number: 1
Keywords: Conservation; Logement; Patrimoine; Quartiers; Westmount

Parcs et terrains de jeux à Montréal-Nord [1] - Lord, Claude (Il était une fois... Montréal-Nord, 2008)
issued: 2008-23-00
Keywords: Clubs; Montréal-Nord; Parcs; Quartiers

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Stratégies culturelles sulpiciennes: l'architecture - Lachapelle, Jacques (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Les Sulpiciens et l'espace montréalais - Robert, Jean-Claude (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Faire et fuir la ville. Espaces publics de culture et de loisirs à Montréal et Toronto aux XIXe et XXe siècles - Dagenais, Michèle (Les Presses de l'Université Laval, 2006)
Keywords: Jardins; Parcs; Places publiques

L'organisation spatiale du corridor du canal de Lachine au XIXe siècle - Desjardins, Pauline (Association des archéologues du Québec, 2006)
Keywords: Lachine (canal)

Des eaux indésirables: Montréal et ses eaux de surface, 1796-1840 - Fougères, Dany (Revue d'histoire de l'Amérique française, 2006)
issued: 2006-22-00/2006-23-00
Keywords: Égouts

Les faubourgs: cette non-banlieue (18e-19e siècles). Comparaison d'Angers et de Montréal. - Freney, Sylvie (Études canadiennes / Canadian Studies, 2006)
Number: 60
Keywords: Faubourgs

La rue Sherbrooke de Montréal: la colonne vertébrale de la ville - Mackay L., Smith (InfiniteBooks, 2006)
Keywords: Rues; Sherbrooke (rue)

Montreal's Sherbrooke Street: the spine of the city - Mackay L., Smith (InfiniteBooks, 2006)
Translators: _:n57063
Keywords: Rues; Sherbrooke (rue)

La fabrique de pipes à fumer Henderson: inventaire archéologique sur le site Henderson-Dixon, BjFj-135, Montréal, 2005. Arrondissement Ville-Marie - Roy, Christian (Ville de Montréal, 2006)
Keywords: Artisans; Tabac

VENNE, JOSEPH - Bisson, Pierre-Richard; Lachapelle, Jacques (Dictionnaire biographique du Canada, 2005)

Le logement traditionnel à Montréal et à Glasgow: partage et différence - Dufaux, François (Montreal-Glasgow, 2005)
Keywords: Logement

Le cimetière Saint-Antoine. Inventaire archéologique (phase 2), Square Dorchester et Place du Canada, BiFj-37, Montréal 2001 - Ethnoscop (Ville de Montréal, 2005)
Keywords: Cimetières; Dominion (square); Places publiques; Squares

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Le cimetière Saint-Antoine. Étude de potentiel et inventaire archéologiques (Phase 1) du square Dorchester et de la place du Canada, BiFj-37, Montréal - Ethnoscop; Groupe Cardinal Hardy (Ville de Montréal, 2005)
Keywords: Cimetières; Dominion (square); Places publiques; Squares

GAUTHIER, LOUIS-ZÉPHIRIN - Gauthier, Raymond (Dictionnaire biographique du Canada, 2005)

Saving the Union's Jack: The Montreal Sailor's Institute and the Homeless Sailor, 1862-98 - Ingram, Darcy (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)

DUNLOP, ALEXANDER FRANCIS - Lachapelle, Jacques (Dictionnaire biographique du Canada, 2005)

Les bouteilles de verre du château de Vaudreuil: une archéologie de l'alcool à Montréal, au XVIIIe siècle - Losier, Catherine (Université de Montréal, 2005)
Keywords: Alcool; Archéologie

Bonds of Friendship, Kinship, and Community: Gender, Homelessness, and Mutual Aid in Early-Nineteenth-Century Montreal - Poutanen, Mary Anne (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Femmes; Itinérance

Évaluation du patrimoine urbain: arrondissement d'Ahuntsic - Cartierville - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Ahuntsic; Arrondissements; Cartierville; Patrimoine

Évaluation du patrimoine urbain: arrondissement d'Anjou - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Anjou; Arrondissements; Patrimoine

Évaluation du patrimoine urbain: arrondissement d'Outremont - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Outremont; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Beaconsfield - Baie d'Urfé - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Beaconsfield; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Côte-des-Neiges - Notre-Dame-de-Grâce - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Côte-des-Neiges; Notre-Dame-de-Grâce; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Côte-Saint-Luc - Hampstead - Montréal-Ouest - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Dollard-Des-Ormeaux - Roxboro - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Dollard des Ormeaux; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Dorval - L'Île-Dorval - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Dorval; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Kirkland - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine

Évaluation du patrimoine urbain: arrondissement de L'Île-Bizard - Sainte-Geneviève - Sainte-Anne-de-Bellevue - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Lachine - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Lachine; Patrimoine

Évaluation du patrimoine urbain: arrondissement de LaSalle - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; LaSalle; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Mercier - Hochelaga - Maisonneuve - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Mercier-Hochelaga-Maisonneuve (arrondissement); Patrimoine

Évaluation du patrimoine urbain: arrondissement de Mont-Royal - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Plateau Mont-Royal (arrondissement)

Évaluation du patrimoine urbain: arrondissement de Montréal-Nord - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Montréal-Nord; Patrimoine

Évaluation du patrimoine urbain: arrondissement de Pierrefonds - Senneville - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Pierrefonds

Évaluation du patrimoine urbain: arrondissement de Pointe-Claire - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Pointe-Claire

Évaluation du patrimoine urbain: arrondissement de Rivière-des-Prairies - Pointe-aux-Trembles - Montréal-Est - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Montréal-Est; Patrimoine; Pointe-aux-Trembles; Rivière-des-Prairies

Évaluation du patrimoine urbain: arrondissement de Rosemont - La Petite-Patrie - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Rosemont

Évaluation du patrimoine urbain: arrondissement de Saint-Laurent - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Saint-Laurent (ville)

Évaluation du patrimoine urbain: arrondissement de Saint-Léonard - Service de la mise en valeur du territoire et du patrimoine (Ville de Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Saint-Léonard

Évaluation du patrimoine urbain: arrondissement de Verdun - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Verdun

Évaluation du patrimoine urbain: arrondissement de Ville-Marie - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Ville-Marie (arrondissement)

Évaluation du patrimoine urbain: arrondissement de Villeray - Saint-Michel - Parc-Extension - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Parc-Extension (quartier); Patrimoine; Quartiers; Saint-Michel; Villeray

Évaluation du patrimoine urbain: arrondissement de Westmount - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Patrimoine; Westmount

Évaluation du patrimoine urbain: arrondissement du Sud-Ouest - Service de la mise en valeur du territoire et du patrimoine (Montréal, Service de la mise en valeur du territoire et du patrimoine, Direction du développement urbain, Division du patrimoine et de la toponymie, 2005)
Keywords: Arrondissements; Le Sud-Ouest (arrondissement); Patrimoine

Death, Burial, and Protestant Identity in an Elite Family: The Montreal McCords - Young, Brian (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: McCord (famille); Protestants

Propos sur le mausolée du bois de l'est du cimetière Notre-Dame-des-Neiges (ARQ- Architecture, 2004)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière)

Étude des influences européennes et américaines dans l'architecture des magasins de détail du Vieux-Montréal (1836-1893): le cas de la rue Notre-Dame Ouest - Bassil, Joanna (Université du Québec à Montréal, 2004)
Keywords: Commerce de détail; Magasins; Quartiers; Vieux-Montréal

Cimetière Notre-Dame-des-Neiges - Bisson, Pierre-Richard; Brodeur, Mario; Drouin, Daniel (Beaux livres Henri Rivard, 2004)
Keywords: Cimetières; Notre-Dame-des-Neiges (cimetière)

Les magasins-entrepôts de Montréal, 1850 à 1880 : formes et fonctions commerciales. Un nouveau regard - Burgess, Joanne; Lauzon, Gilles (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Magasins

Les faubourgs et leur évolution du XVIIIe siècle au milieu du XIXe siècle. Étude comparée d’Angers et de Montréal - Freney, Sylvie (Université du Québec à Montréal et Université d'Angers, 2004)
Keywords: Faubourgs

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Number: 4
Keywords: Paysages; Port

Promenade verdunoise: un aperçu - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2004)
issued: 2004-23-00
Keywords: Quartiers; Rues; Verdun; Villages

Monklands Then, Villa Maria Now: The Story of a Convent School Which Grew from the Estate of Sir James Monk to a Modern, Private High School - Lanthier, Helen (Congregation of Notre-Dame, 2004)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Monklands; Villa-Maria

Conflagration et réaménagement urbain: le cas de Montréal en 1852 - Lavictoire, Nathalie (Université du Québec à Montréal, 2004)
Keywords: Incendies

Caractérisation structurale et évaluation de la vulnérabilité sismique des bâtiments historiques en maçonnerie du Vieux-Montréal - Lefebvre, Karine (École de technologie supérieure, 2004)
Keywords: Conservation; Quartiers; Vieux-Montréal

A City Transformed: Manufacturing Disctricts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Manufacturing Suburbs. Building Work and Home on the Metropolitan Fringe, 2004)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

The Settlement and Rural Domestic Architecture of Côte Saint-Antoine, 1675-1874 - MacKinnon, Janet S. (Université de Montréal, 2004)
Keywords: Côtes; Logement

Carving the Past in Stone: le Monument aux Patriotes - O'Flaherty, Rosemary (Université Concordia, 2004)
Keywords: Monuments; Rébellions

Montreal's Fashion Mile: St Catherine Street, 1890-1930 - Sifton, Elizabeth (Fashion. A Canadian Perspective, 2004)
Keywords: Rues; Sainte-Catherine (rue); Vêtements

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

L'Hôtel Rasco: inventaire et fouille archéologiques au site Le Royer (BjFj-53), 1998: Vieux-Montréal et faubourgs - Arkéos (Ville de Montréal, 2003)
Keywords: Archéologie; Hôtellerie

Le manoir Viger : étude historique et patrimoniale - D'Amour, Valérie (Remparts, 2003)
Keywords: Patrimoine; Seigneurie; Viger; Denis-Benjamin

Behind the Scene of the Lachine Canal Landscape - Desloges, Yvon (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Lachine (canal)

La vie de château - Dugas, Marcel (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Château Dufresne; Golden Square Mile; Logement; Mount Stephen Club

La maison Bagg: inventaire archéologique au site BiFj-32, 1992: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2003)
OCLC: 956636261
Keywords: Logement; Marchands

Le moulin de Pointe-aux-Trembles: survol historique et analyse du parcellaire (BjFi-5), 2001 - Ethnoscop (Ville de Montréal, 2003)
Keywords: Meunerie; Pointe-aux-Trembles; Quartiers

L'émergence des faubourgs de Montréal au XVIIIe siècle - Freney, Sylvie (Études canadiennes / Canadian Studies, 2003)
Number: 55
Keywords: Faubourgs

Le rôle de la côte dans la formation de la grille de rues, sur l'île de Montréal, incluant Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Côtes; Rues

Le Royal Insurance Building: recherche archéologique au site BjFj-22, 1990: Vieux-Montréal et faubourgs - Les recherches Arkhis (Ville de Montréal, 2003)
Keywords: Assurance; Pointe-à-Callière; Royal Insurance

The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2003)
Number: 1
Keywords: Redpath (famille); Redpath; John

Tertiarisation et transformation de l'espace urbain: la rue McGill à Montréal (1842-1934) - Poitras, Claire (Urban History Review / Revue d'histoire urbaine, 2003)
issued: 2003-21-00
Keywords: Rues

Joseph (Jos) Venne (1858-1925) architecte montréalais prolifique et méconnu - Bassil, Soraya (Montréal en tête, 2002)
issued: 2002-21-00

Women’s Workplaces: The Impact of Technological Change on Working-Class Women in the Home and in the Workplace in Nineteenth Century Montreal - Bradbury, Bettina (Rethinking Canada. The Promise of Women’s History, 2002)
Keywords: Femmes; Travail

Le cimetière Mont-Royal - depuis 1852 / Mount Royal Cemetery - since 1852 - Cloutier, Myriam (Cimetière Mont-Royal, 2002)
Keywords: Cimetières

Le canal de Lachine: l’eau à l’œuvre - Desloges, Yvon (Continuité, 2002)
issued: 2002-22-00
Keywords: Lachine (canal)

La pépinière Guilbault: il y avait un jardin… - Fortin, Daniel (Continuité, 2002)
issued: 2002-22-00
Keywords: Jardins

The Creative Destruction of Montreal: Street Widenings and Urban (Re) Development in the Nineteenth Century - Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2002)
issued: 2002-23-00
Keywords: Rues; Voirie

Les couronnements de Montréal - O'Neil, Jean; Brunet, Pierre Phillipe (Hurtubise HMH, 2002)

Pure Water in the City. Covering the Reservoirs on Mount Royal - Ross, Susan Martha (Université de Montréal, 2002)
Keywords: Aqueduc; Côte-des-Neiges; Mont Royal

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

A City Transformed: Manufacturing Districts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Journal of Historical Geography, 2001)
Number: 1
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Outdoor Play Areas for Children in High-Density Housing in Montreal - Aggarwal, Monica (Université McGill, 2001)
Keywords: Enfants; Parcs; Plateau Mont-Royal; Quartiers

Royal et populaire - Bumbaru, Dinu; Guilbault, Sylvie (Continuité, 2001)
issued: 2001-23-00
Keywords: Groupes populaires; Mont Royal

Une petite maison... Un grand homme: Hormidas Laporte - Cloutier, Gabrielle (Montréal en tête, 2001)
issued: 2001-21-00
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Des rues et des hommes : les commencements des politiques publiques locales en matière de travaux publics à Montréal, 1796-1840 - Fougères, Dany (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2001)
Keywords: Rues; Voirie

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

La vie quotidienne dans la vallée du Saint-Laurent, 1790-1835 - Hardy, Jean-Pierre (Septentrion et Musée canadien des civilisations, 2001)

History of landscape architecture in Montreal - Jacobs, Peter; Williams, Ron (Landscape Architecture, 2001)

Étude patrimoniale de la maison des Hurtubise - Robichaud, Léon; Stewart, Alan (Ministère de la Culture et des Communications, Institut d'histoire de l'Amérique française et Remparts, 2001)
Keywords: Logement

Bourgeois Visions of Urban Space in Nineteenth-Century Quebec - Young, Brian J. (Frontières flottantes: Lieu et espace dans les cultures francophones du Canada / Shifting Boundaries: Place and Space in the Francophone Cultures of Canada, 2001)
Keywords: Bourgeoisie

A New World from Two Old Ones: the Evolution of Montreal's tenements, 1850-1892 - Dufaux, François (Urban Morphology, 2000)
Number: 1
Keywords: Logement

Faubourg Québec: la ville conviviale - Dufaux, François (Continuité, 2000)
issued: 2000-23-00
Keywords: Centre-sud (quartier); Faubourgs; Logement; Quartiers

Une problématique pour une histoire des infrastructures urbaines à travers le cas de Montréal (1845-1960) - Gagnon, Robert; Fougères, Dany; Trépanier, Michel (Technology and Engineering, 2000)
Keywords: Aqueduc; Transport en commun; Égouts

Manufacturing Montreal. The Making of an Industrial Landscape, 1850-1930 - Lewis, Robert D. (John Hopkins University Press, 2000)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne